Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Menginap di Park Hotel Jakarta - Michael Joshua Sabandar; Sri Fadjar Ayuningsih (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research was aimed to analyze the influence of product quality and price on the costumer’s stay decision. The population in this research was Park Hotel’s Jakarta customer. The samples were determined based on accidental sampling method technique. Data were collected by using questionnaires, there were 100 questionnaires distributed in Park Hotel’s Jakarta customer who stay between December 2019 – January 2020. Data were processed using multiple regression analysis supported by SPSS v.22 for windows. The result of this research showed that in costumer stay decision and simultaneously product quality and price have effect on Costumer Stay Decision, with the statistic of product quality (X1) affect the decision to stay (Y) at Park Hotel Jakarta, with the ability of the variable quality of the product to explain the stay decision of 6.03%. Price (X2) affects the stay decision (Y) at Park Hotel Jakarta, with the variable price ability to explain the stay decision of 6.62%. Product Quality (X1) and Price (X2) combined simultaneously found that there was a real influence of the three variables simultaneously to determine the decision to stay (Y) at Park Hotel Jakarta with a contribution of 24.01%.